Active Learning Reduces Academic Risk of Students with Nonformal Reasoning Skills: Evidence from an Introductory Physics Massive Course in a Chilean Public University - Hernandez-Silva, C; Lagubeau, G; Tecpan-Flores, S (American Physical Society, 2020)
We present the findings of a pilot plan of active learning implemented in introductory physics in a Chilean public university. The model is research based as it considered a literature review for adequate selection and design of activities consistent with the levels of students reasoning skills. The level of scientific reasoning is positively correlated to student success. By contrast to a control group of students following traditional lectures, we observed a significant reduction in failure rate for students that do not yet possess formal scientific reasoning. This profile of students being the majority, we conclude that implementing active learning is particularly suited to the first year of higher education in the context of a developing country. It fits the particularities of student profile and typical classroom size, leading to learning improvement and reduction of academic risk, as well as being financially sound © 2020 authors.